Bioethanol production from residues and waste - Aboughaly M.; Soudagar M.E.M.; Zainal B.S.; Veza I. (Elsevier, 2025)
The conversion of biowaste into bioethanol, which possesses biodegradable properties, low toxicity, and is a renewable resource, is regarded as a promising clean fuel technology. It is anticipated that the annual production of bioethanol will surpass 7 billion gallons. This chapter focuses on the design of the production process for bioethanol, encompassing pretreatment and enzymatic hydrolysis. The anticipated properties of bioethanol, based on various process parameters and operating conditions, are examined, as these factors influence the calorific value and autoignition temperatures of bioethanol. The chapter further explores the steps involved in process design, including glycolysis, acetaldehyde production, glycolysis, and protonation of ethanol through the use of hydrogen ions. The performance of bioethanol is assessed in comparison to other fossil fuels. In terms of environmental impact, the emission of bioethanol ranges from 23 to 85 g CO2eq/MJ, which is 75% lower than that of fossil fuels. Biomass is categorized into forest biomass, biorenewable waste, energy crops, and aquatic biomass feedstock. Various fermentation techniques, such as liquid-state fermentation, solid-state fermentation, and gravitational fermentation, are evaluated for their impact on bioethanol yield. Additionally, different fermentation methods, including liquid-state fermentation, solid-state fermentation, and gravitational fermentation, are assessed for their performance. Bioethanol has also been utilized as an additive to fossil fuels, enhancing evaporative temperatures and reducing volatility, thus improving ignition properties. ? 2024 Elsevier Ltd. All rights reserved.